Una nota sobre la prueba de Peña y Rodríguez para la bondad del ajuste en series de tiempo (2015)
The aim of this paper is to divulge the modiﬁcation of the Pen˜a y Rodr´ıguez test (2002) of goodness of ﬁt. This test is asymptotically equivalent, but it is more powerful than the previous one. Two approaches are proposed using the gamma and the normal distributions. By an empirical example it is shown that theproposedtest ismore powerfulthanLjung-Boxtestand Montitestof nonlinear models detection.